Borders and Ecotones in the Indian Ocean (Presses universitaires de la Méditerranée, 2022)
This collection of critical essays anchors itself in the Indian Ocean and explores the multiple ways dynamic exchanges have shaped this multilingual region of the world, from India to the Mascarene Islands to Southern Africa. Borders, edges and third spaces are revisited through the notion of the ecotone, a transitional zone between two ecosystems. If the term has primarily been used by biologists and ecologists, the metaphorical angle proves to be fruitful as it authorizes trans-disciplinary approaches and empowers fresh perspectives. In French and in English, the aim of the volume is to contribute to scholarship already published across various disciplinary fields and to participate in the development of Indoceanic studies. The authors of the volume aim to rethink those ecotonal sites that are spaces of frictions as much as spaces of fusion. The essays are by Pallavi Chakravarty, Debdatta Chowdhury, Cécile Do Huu, Pierre-Éric Fageol and Frédéric Garan, Laurence Gouaux-Rabasa, Elisa Huet, Marianne Hillion, J.U. Jacobs, Annu Jalais, Valérie Magdelaine-Andrianjafitrimo, Nicolas Roinsard, Laëtitia Saint-Loubert, Meg Samuelson, Ritu Tyagi. A conversation with the Mauritian writer Shenaz Patel offers a conclusion that opens the horizon towards literary creation.